Kinetic Studies of Bischloroimide Monomers for the Facile Synthesis of Different Molecular Architecture Poly(phthalimide‐co‐naphthalimide)s. Issue 23 (16th August 2017) - Mushtaq, Nafeesa; Chen, Guofei; Sidra, Lala Rukh; Zhang, Anjiang; Fang, Xingzhong
Abstract: A series of different molecular architecture (homo, random, block and gradient type) copolymersPI‐3(a–e) were synthesized by solution polycondensation. Three different bischloroimide monomers [bischlorophthalimide2 a, bischloronaphthalimide2 b and bischloro (naphthalimide‐phthalimide)2 c ] were prepared and reacted with 4, 4′‐thiobisbenzenethiol by different synthetic routes. The chemical reactivity of these monomers2(a–c) was examined by kinetic study of model compounds N ‐phenyl‐4‐chloro‐1, 8‐naphthalimide and N ‐phenyl‐4‐chlorophthalimide using gas chromatography mass spectrometry (GC‐MS). The difference in chemical reactivity of monomers was utilized to design molecular architecture of copolymer, and the influence of comonomers sequence on copolymer properties is investigated. The synthesized copolyimidesPI‐3(a–e) integrated the excellent properties of naphthalimide and phthalimide as good organosolubility, high glass transition temperature of 198–319 °C and good thermooxidative stability based on 5 % weight loss temperature of 492–524 °C and 480–532 °C in nitrogen and air, respectively. Gradient type sequencePI‐3 e offers a good combination of phthalimide and naphthalimide groups in copolymers for improved thermal and mechanical properties. Abstract : Reactivity difference of bisimide monomers is investigated and utilized to synthesize different molecular architectures (block, random and gradient) of polyimides PI‐3(c–e) by polycondensation. This strategy offers a good combination of phthalimide and naphthalimide groups in copolymers for improved thermal and mechanical properties.